Population Structure of Phytophthora plurivora on Rhododendron in Oregon Nurseries - Carleson, Nicholas C (Plant disease, 2019)
Phytophthora plurivora is a recently described plant pathogen, formerly recognized as P. citricola. Recent sampling of Pacific Northwest nurseries frequently encountered this pathogen, and it has been shown to be among the most damaging Phytophthora pathogens on ornamentals. We characterized the population structure of P. plurivora in a survey of four Oregon nurseries across three different counties with focus on Rhododendron hosts. Isolates were identified to the species level by Sanger sequencing and/or a PCR-RFLP assay of the internal transcribed spacer (ITS) region. We used genotyping-by-sequencing to determine genetic diversity. Variants were called de novo, resulting in 284 high-quality variants for 61 isolates after stringent filtering. Based on Fst and AMOVA, populations were moderately differentiated among nurseries. Overall, population structure suggested presence of one dominant clonal lineage in all nurseries, as well as isolates of cryptic diversity mostly found in one nursery. Within the clonal lineage, there was a broad range of sensitivity to mefenoxam and phosphorous acid. Sensitivity of the two fungicides was correlated. P. plurivora was previously assumed to spread clonally, and the low genotypic diversity observed within and among isolates corroborated this hypothesis. The broad range of fungicide sensitivity within the P. plurivora population found in PNW nurseries has implications for managing disease caused by this important nursery pathogen. These findings provide the first perspective into P. plurivora population structure and phenotypic plasticity in Pacific Northwest nurseries